Pyroclastic Density Current Facies in the Millennium Eruption of Tianchi Volcano, Northeast China: Insights From Topography, Stratigraphy, Granulometry, and Petrography - Zhao, Bo; Xu, Jiandong; Yu, Hongmei; Chen, Zhengquan (Frontiers in Earth Science, 2020)
The 946 A.D. Millennium Eruption (ME) of Tianchi volcano produced masses of pyroclastic density current (PDC) deposits that cover an area that extends roughly 50 km from the crater. In order to understand PDC dynamic processes, this study examines the proximal to distal variations in the PDC facies by analysing the topography, stratigraphy, granulometry and petrography. Topography of Tianchi volcano has different slopes, including the cone (>6°), lava shield (2–5°) and lava plateau (<1°), which affected the PDC emplacement during the ME. The shape of the PDC deposits radiates outward from the crater, and the periphery has two pyroclastic aprons. The proximal strata (<10 km) are less than 4 m thick and consist of eutaxitic and lava-like structures in the gullies of the cone. The medial strata (10–20 km) are 10–60 m thick, with columnar joints, pumice-rich layers, and lithic-rich layers in the valleys of the shield. The distal strata (>20 km) are less than 10 m thick, with coarse-tail layers, ground surge layers, climbing layers, and carbonized woods in the plateau. The degree of PDC welding decreases with the distance from the crater. From the proximal to the distal strata, the emplacement temperature of the PDCs decreased from 740 °C to 280 °C. The medial layers indicate a gravitational differentiation effect and weakened transportation of the PDCs, which led to the formation of thick beds. The distal PDCs demonstrate fluidisation characteristics and a density far lower than those of the proximal and medial strata, which exhibit clear stratification. Grain size data (<64 mm) show that the median diameters decreases with increasing distance from the crater. Rhyolitic and trachytic pumice are found in the PDCs and are assumed to be associated with the composition of the magma chamber. Magmatic mixing structures were confirmed by microscope observations. The volume estimation of PDCs in China is 6.9806 km3. The PDCs exhibit characteristics of high temperatures, large volumes, flowing over long distances, and having the ability to climb hills. The PDCs were the most hazardous volcanic phenomena and can provide a reference for future potential PDC hazards around the Tianchi volcano.